2009
DOI: 10.1007/s10637-009-9230-z
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of Triapine® (NSC# 663249) and gemcitabine as second line treatment of advanced non-small cell lung cancer: Eastern Cooperative Oncology Group Study 1503

Abstract: SummaryBackground-The objective of ECOG 1503 was to determine the response rate of this combination in the second-line treatment of advanced NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
98
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 25 publications
1
98
1
Order By: Relevance
“…In contrast, prior to our study other phase I/II trials of this combination with different dose/ schedule [32,[42][43][44], reported more significant toxicities including hypoxia, methemoglobinemia and significant cardiopulmonary toxicity. The initial phase I trial defined the MTD as triapine at 105 mg/m 2 infused over 2-4 h followed by gemcitabine at 1000 mg/m 2 over 30 min (standard-dose), on days 1, 8, and 15, for a 28-day cycle [32].…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…In contrast, prior to our study other phase I/II trials of this combination with different dose/ schedule [32,[42][43][44], reported more significant toxicities including hypoxia, methemoglobinemia and significant cardiopulmonary toxicity. The initial phase I trial defined the MTD as triapine at 105 mg/m 2 infused over 2-4 h followed by gemcitabine at 1000 mg/m 2 over 30 min (standard-dose), on days 1, 8, and 15, for a 28-day cycle [32].…”
Section: Discussioncontrasting
confidence: 59%
“…The initial phase I trial defined the MTD as triapine at 105 mg/m 2 infused over 2-4 h followed by gemcitabine at 1000 mg/m 2 over 30 min (standard-dose), on days 1, 8, and 15, for a 28-day cycle [32]. This recommended phase II dose was tested in 4 different phase II solid tumor trials including 2 in non-small cell lung cancer, 1 in advanced pancreas cancer and 1 in biliary cancer [42][43][44][45]. Taken together, the only observed responses were in 3 patients with biliary cancers.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies suggest some positive results after 3-AP was coadministered with cisplatin and daily pelvic radiation in patients with locally advanced cervical and vaginal cancer (Kunos et al, 2010). The notable side effects of 3-AP include hypoxia and methemoglobinemia (Yen et al, 2004;Gojo et al, 2007;Knox et al, 2007;Odenike et al, 2008;Traynor et al, 2010), which are major concerns for patients with compromised cardiopulmonary function.…”
Section: Introductionmentioning
confidence: 99%
“…1A) belongs to the large class of a-Nheterocyclic thiosemicarbazones. Its antitumor activity has been known for more than a decade and was studied in several clinical phase I and phase II trials (Nutting et al, 2009;Kunos et al, 2010;Traynor et al, 2010;Ocean et al, 2011). The anticancer activity of 3-AP has been attributed to the inhibition of the ribonucleotide reductase enzyme (Finch et al, 2000).…”
Section: Introductionmentioning
confidence: 99%